Irrigation development in Ghana: Past experiences, emerging opportunities, and future directions - Namara, Regassa E.; Horowitz, Leah; Nyamadi, Ben; Barry, Boubacar (International Food Policy Research Institute, 2011)
Agriculture has a central socioeconomic position in Ghana. This sector accounts for about 65 percent of the work force, about 40 percent of the gross domestic product, and about 40 percent of foreign currencies acquired through exports. Although agriculture is a key part of the country's economy, the structure of the sector is vulnerable because it relies on rainfed agriculture during a roughly six-month rainy season. Droughts and other types of unseasonable weather pose risks for farmers. Under these conditions, irrigation development offers the promise of greater food security and the rural-area development by ensuring yearlong agricultural production.